Mediation of organismal aging and somatic proteostasis by the germline - Khodakarami, Amirabbas; Saez, Isabel; Mels, Johanna; Vilchez, David (Frontiers in Molecular Biosciences, 2015)
Experimental interventions that reduce reproduction cause an extension in lifespan. In invertebrates, such as Caenorhabditis elegans, the aging of the soma is regulated by signals from the germline. Indeed, ablation of germ cells significantly extends lifespan. Notably, germline-deficient animals exhibit heightened resistance to proteotoxic stress. This phenotype correlates with increased potential of intracellular clearance mechanisms such as the proteasome and autophagy in somatic tissues. Here we review the molecular mechanisms by which signals from the germline regulate lifespan in C. elegans with special emphasis on clearance mechanisms.